New long-tailed pterosaurs (Wukongopteridae) from western Liaoning, China - Wang,Xiaolin (2010)
Two almost complete long-tailed pterosaurs from the Linglongta, Jianchang County, western Liaoning, China, are described and represent new taxa referred to the non-pterodactyloid clade Wukongopteridae. Kunpengopterus sinensis gen. et sp. nov. differs from other members of this clade mainly by the rounded posterior region of the skull, thick lacrimal process of the jugal and lack of a bony premaxillary crest. This species further shows a soft tissue crest above the frontal, a comparatively larger wing finger, and the proximal segment of the second pedal phalanx of the fifth toe shorter than in other wukongopterids. The second new species is referred to the genus Darwinopterus, D. linglongtaensis sp. nov. based on the posterior region of the skull. It further differs from other wukongopterid pterosaurs by the thin lacrimal process of the jugal, foramen on nasal process rounded, and by having the second pedal phalanx of the fifth toe less curved (115°). Several differences among the Wukongopteridae can be found in the dentition and the feet, suggesting that they might have occupied slightly different ecological niches. The long-tailed Changchengopterus pani is tentatively referred to this clade and new diagnosis for the wukongopterids Wukongopterus lii and Darwinopterus modularis is provided.